Palm Avenue, Botanical Gardens, Trinidad - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
The postcard shows a pathway lined with Palm trees in the Botanical Gardens, Trinidad. A man who appears to be of East Indian descent, can be seen walking along the path.
Colour: Sepia; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago; Gardens--Trinidad and Tobago; Men--Trinidad and Tobago; Garden walks--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain